2018
DOI: 10.1515/ling-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

The grammaticalization of -kotok- into a negative marker in Manda (Bantu N.11)

Abstract: It is common both crosslinguistically and specifically in Bantu languages for the prohibitive to be formed by a construction consisting of a cessative verb in collocation with a non-finite verb. This is also the case in Manda, an understudied Southern Tanzanian Bantu language. In Manda, a negative imperative is expressed by the auxiliary -kotok-, with the (lexical) meaning ‘leave (off), stop’, operating on an infinitive full verb. Intriguingly, there is variation in this construction, as -kotok- may be both fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Diachronically speaking, we have shown that -téekw-and -lina began to meaningfully express necessity around the 1930s and 1980s respectively, while -andi-'s involvement in expressing necessity has been stable throughout the period covered by the corpus. Although we could not show with empirical corpus evidence which marker(s) was/were used to convey necessity in earlier time periods, our assumption, partly based on evidence from older literature on Luganda and comparative evidence from Manda (Bernander 2017), is that necessity was expressed by less-grammaticalised markers, such as the verb -étaag-and/or modal auxiliaries such as -gwán(ír)-, whose use has greatly reduced.…”
Section: Discussionmentioning
confidence: 72%
“…Diachronically speaking, we have shown that -téekw-and -lina began to meaningfully express necessity around the 1930s and 1980s respectively, while -andi-'s involvement in expressing necessity has been stable throughout the period covered by the corpus. Although we could not show with empirical corpus evidence which marker(s) was/were used to convey necessity in earlier time periods, our assumption, partly based on evidence from older literature on Luganda and comparative evidence from Manda (Bernander 2017), is that necessity was expressed by less-grammaticalised markers, such as the verb -étaag-and/or modal auxiliaries such as -gwán(ír)-, whose use has greatly reduced.…”
Section: Discussionmentioning
confidence: 72%
“…Schadeberg (n.d.: 8-9;2002: 187-188) reconstructs the verb*kòt-ʊk as a derived verb stem consisting of a reflex of the separative extension *-ʊk suffixed to the verb *kòt 'stoop, be bent', thus yielding the separative meaning 'straighten (oneself)' and, by extension, 'quit and go home from work'. As shown by Bernander (2018) for Manda and neighboring languages that have developed a negator out of reflexes of this verb, however, the verb has undergone a lexico-semantic shift to a more generalized cessative verb 'quit, stop', as in (5) above.…”
Section: Verb Rootmentioning
confidence: 99%
“…Finally, there are attestations of the same verb, even in the same construction, having developed different negative functions with different distributional patterns in a contiguous set of sister languages. One example is kotoka in southern Tanzania (Bernander 2018;Devos Forthcoming), which function as a non-declarative negator alone in Matengo (N13) and Kisi (G67) but as both a non-declarative negator and a negator of infinitives in Ngoni (N12). In Manda (N11) and Mpoto (N14) kotoka may additionally function as a negator of relative clauses, in the case of the latter, or adverbial clauses, in the case of the former.…”
Section: Synchronic Overlap Variation and Diachronic Changementioning
confidence: 99%